Effet thérapeutiques et biologiques de l’extrait du pourpier (Portulaca oleracea) - BELARBI, Amina; Djeziri, Khadidja (My University, 2020)
Our work focused on the study of the biological activities of the extract of the leaves of Portulaca oleracea L. The analysis of this extract revealed the presence of some chemical groups (total polyphenols and flavonoids) likely to express the desired activities and their contents were determined by spectrophotometric methods. The in vitro antioxidant activity was studied with two different methods: DPPH free radical reduction technique and the iron reduction assay (FRAP). The results obtained showed that the extract can act as a radical scavenger. The exploration of the anti-inflammatory activity in vitro showed that the extract has a strong capacity to inhibit protein denaturation at a rate of 236.75%. The biological analysis carried out on erythrocytes isolated from healthy human blood by ethanolic extracts shows that the plant Portulaca oleracea L. is very weakly toxic with a rate of hemolysis that does not exceed 0.857% respectively.
Keywords: Portulaca oleracea L., total polyphenols, total flavonoids, hemolytic effect, antioxidant activity, anti-inflammatory activity